1988
DOI: 10.1007/bf01907106
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes of relaxation and its load sensitivity in rat cardiac muscle

Abstract: The relaxation phase and its load dependence were studied in papillary muscles isolated from the left ventricle of rats of the following ages: 20 days, 2, 8, 18, and 24 months. The myofibrillar ATPase activity and the force-velocity relation were determined in each age group in order to characterize the kinetic properties of the contractile material. Both shortening velocity and myofibrillar ATPase activity showed a progressive reduction with maturation and aging. This observation suggested an age-dependent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The resulting homogenate was then placed in a centrifuge (model J2-21, Beckman Instrs., Fullerton, California) for 15 minutes at 17,3OOg at 4° C. From this preparation, washed and purified myofibrils were obtained according to a procedure derived from that proposed by Solaro et al 19 and described in detail elsewhere. 20 The ATPase activity of the myofibrillar preparation was determined from the rate of release of inorganic phosphate in an incubation medium of the following composition (mM): KQ 50, MgCla 2, NaATP 2, imidazole 20, CaCl 2 0-1.5, EGTA 0-1.6, pH 7, at 27° C. The concentrations of CaCl 2 and EGTA were varied in order to obtain pCa values from 4.3 to 8. The pCa value in the incubation medium was calculated by means of a computer program similar to that described by Fabiato and Fabiato.…”
Section: Determination Of the Myofibrillar A Tpase Activitymentioning
confidence: 99%
“…The resulting homogenate was then placed in a centrifuge (model J2-21, Beckman Instrs., Fullerton, California) for 15 minutes at 17,3OOg at 4° C. From this preparation, washed and purified myofibrils were obtained according to a procedure derived from that proposed by Solaro et al 19 and described in detail elsewhere. 20 The ATPase activity of the myofibrillar preparation was determined from the rate of release of inorganic phosphate in an incubation medium of the following composition (mM): KQ 50, MgCla 2, NaATP 2, imidazole 20, CaCl 2 0-1.5, EGTA 0-1.6, pH 7, at 27° C. The concentrations of CaCl 2 and EGTA were varied in order to obtain pCa values from 4.3 to 8. The pCa value in the incubation medium was calculated by means of a computer program similar to that described by Fabiato and Fabiato.…”
Section: Determination Of the Myofibrillar A Tpase Activitymentioning
confidence: 99%
“…Indeed, it has been reported that myocardial shortening velocity decreases with aging in association with lowering of actomyosin ATPase. 38 However, no significant correlations were found between age and any parameter tested in either myofibrils or fibers, with or without DCM ( Figure V in the Data Supplement). It can therefore be said that the changes in the Ca-SPOC parameters on DCM are not associated with aging.…”
Section: Resultsmentioning
confidence: 91%
“…In humans, for instance, decreasing heart rate may provide more time for early filling resulting in progressively increasing E and E’ velocities (Eidem et al, ). Finally, IVRT (both absolute and relative to the cardiac cycle length) progressively decreases in the developing rat, a finding suggestive of more efficient relaxation with age (Cappelli, Tortelli, Zani, Poggesi, & Reggiani, ), whereas in humans, the absolute IVRT remains unchanged from neonatal to adolescent stages, shortening only relative to the cardiac cycle length (Eidem et al, ).…”
Section: Discussionmentioning
confidence: 99%